INFLASI DAN EFISIENSI OPERASIONAL BANK: STUDI PADA EMITEN PERBANKAN LQ45 - Haris, Abdul; Yunita, Rizki Arvi (UNIVERSITAS DHARMAWANGSA, 2025)
The purpose of this study is to analyze the effect of inflation on the efficiency of banking operations as measured by the Cost to Income Ratio (CIR), and to test the moderating variable, namely company size. This study was conducted on banks that were consistently listed in the LQ45 index during the period 2013-2023, namely BCA, Mandiri, and BRI. This research uses quantitative methods with descriptive and inferential approaches. Secondary data was obtained from annual financial reports and relevant macroeconomic data, then analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The findings of this study indicate that inflation has a positive and significant effect on CIR, which indicates a decrease in operational efficiency as inflation increases. However, firm size has no significant effect as a moderating variable, thus neither strengthening nor weakening the relationship between inflation and operational efficiency. This finding confirms that inflationary pressures remain a major challenge for banking efficiency, and adaptive operational management is more important than just firm size. This study provides practical implications for bank management and regulators to formulate cost control policies and efficiency strategies that are responsive to inflation dynamics.